Teaching English locative prepositions - Bratož, Silva (Linguistica (Ljubljana), 2014)
Prepositions are notoriously hard to learn, and frequently subject to negative transfer. In addition, prepositional meanings are commonly extended from the spatial to abstract domains and are, as a consequence, often unpredictable and arbitrary. Traditional approaches to second language preposition teaching have, therefore, suggested that the best way to learn prepositions would be through rote learning. On the other hand, a cognitive linguistics approach argues that the multiple uses of prepositions can be seen as related in systematic ways. Several pedagogical implications of applying cognitive linguistics findings in second language teaching and learning will be discussed, suggesting ways of translating theory into practical consideration and effective teaching materials. The second part of the article presents an instructional model for teaching the locative prepositions in, on and at from a cognitive perspective, and discusses the results of a study conducted to observe the learners' response to instruction, based on cognitive linguistics findings. In addition, the benefits of focusing on the cross-linguistic differences between the native and target language, in an explicit and systematic way, will be discussed. In this context, reference will be made to several insights and ideas promoted by the CEFR. The article will end by considering some suggestions and ideas for future research.
Keywords: anglais; angleščina; Cadre européen commun de référence pour les langues; CECRL; didactique des langues; didaktika jezika; English; enseignement des langues; kognitivno jezikoslovje; linguistique cognitive; medjezikovni transfer; poučevanje jezika; predlog; préposition; SEJO; Skupni evropski jezikovni okvir; transfert interlinguistique; tuji jeziki